EVALUATION ON THE NUMBER OF CD4 T CELLS AND ANTIRETROVIRAL SIDE EFFECTS IN PATIENTS WITH AIDS - Khairunisa, Siti Qamariyah; Normalina, Irine; Nasronudin, Nasronudin (Institute of Topical Disease Universitas Airlangga, 2012)
Antiretroviral drug discovery has encouraged a revolution in the care of people living with HIV, although it has not been able to cure diseases and to increase the challenge in terms of drug side effects. Side effects of antiretroviral drugs are fairly common occurrences in HIV patients and generally occur within the first three months after initiation of antiretroviral therapy, although long-term side effects are also often found afterwards. This study aims to evaluate the number of CD4 T-cells in patients with AIDS before and after getting on ARV therapy and side effects arising during the taking of ARVs. Samples were collected from 10 patients infected by HIV/AIDS in a clinic in Surabaya. This study is an analytical survey. Data collection was conducted using secondary data obtained from the medical record card status on HIV paients in a clinic in Surabaya. Data results showed that the side effects that often occur in people with AIDS are appetite loss (90%), headache (80%), insomnia (80%) and nausea (70%). While many combinations of antiretroviral drugs have side effects such as a combination of AZT +3 TC + EFV, d4T +3 TC + followed by EFV and AZT +3 TC + NVP. The present study shows that combination antiretroviral therapy gives good results to the increased number of CD4 T-cellsin patients living with HIV, as shown by the tendency of an increase in the number of CD4 T-cells in 8 out of 10 AIDS patients who received a antiretroviral therapy.